Migration Tables, Part V-A and B, Series-19 - Das, B.K. (Karnataka, 1981)
Population classified by place of birth, Migrants classified by place of last residence and duration of residence in place of Enumeration, Main workers marginal workers, Non-workes and literacy among migrants reporting Employment as reason for migration by age sex and duration of residence.
Keywords: Migration Tables